Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Pegawai yang Dimoderasi Kompetensi Pegawai pada Deputi Bidang Administrasi Aparatur Kementerian Sekretariat Negara - Frawanty . (JURNAL CITRA WIDYA EDUKASI, 2018)
This study aims to determine the effect of leadership style on employee competence and employee performance, the effect of work motivation on employee competence and employee performance, and employee competence to determine the effect on the employee performance in the Deputy of Administrative Reform, Ministry of Secretary State. The research methodology used was survey method with Path Analisys with Amos SPSS version 22. The research showed that leadership style has no effect either directly or indirectly on employee competence and employee performance. Motivation influential work either directly or indirectly to the employee competence and employee performance. Employee competence direct influence on employee performance.